Keanekaragaman dan Pemanfaatan Tumbuhan Bawah pada Lahan Agroforestry di Desa Alu Kecamatan Alu Kabupaten Polewali Mandar - mahfudz, mahfudz; Rusmidin (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2023)
Undergrowth has a very important role in the ecosystem, including in nutrient cycling, reducing erosion, increasing infiltration, as a source of germplasm and a source of medicines. This research was conducted in Alu Village, Alu District, Polewali Mandar Regency, which aims to determine the diversity of species and the use of undergrowth in agroforestry land cover by the Alu Village community. The research was conducted in August-October 2022. This type of research is quantitative. This research was conducted by means of inventory and identification of undergrowth by making 5x5 m plots in mountainous areas, farms, and settlements. The results of the study obtained 35 types of understorey vegetation spread over the three points. In mountainous areas and settlements, 18 types of vegetation were found and on farms, 15 types of vegetation were found. The diversity of understorey species in Alu Village is moderate. There are 16 types of undergrowth vegetation used by the people of Alu Village.